ANALISIS INTEGRASI NILAI PANCASILA DALAM BUDAYA MANGGARAI - Keristian Dahurandi & Vinsensius Nase (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
Pancasila is a noble agreement of the Indonesian nation that arises from the distinctive cultural values of the people in Indonesia. On that basis, Pancasila contains basic philosophical values, the soul of the nation or the identity of the nation, and becomes the real way of life of the Indonesian nation. With that, the internalization of the value of Pancasila is not something foreign in the life of every local culture to be lived including in the local culture of Manggarai. The divine value is easily integrated in the Manggarai culture which recognizes the existence of God (Mori Kraeng, Ame Rinding Mane) which is strengthened by the inclusion of Catholicism and other major religions. The value of a just and civilized humanity is illustrated in the courtesy of the Manggarai people facing guests (tiba meka). The value of unity is depicted in terms (goet): poe cama ngger one, lewang cama ngger peang or ipung ca tiwu neka woleng wintuk, teu ca ambo neka woleng lako (strengthening unity into one's own group). The fourth precept value is integrated in the wisdom of lonto leok (sitting in deliberation). The value of social justice is embodied in the development of actions that put the "weak" first in the form of dodo, wuat wai and kope gatherings. In short, Manggarai's local wisdom has integrated the values of Pancasila into the way of life of the Manggarai people as part of Indonesian citizens.